Peranan Muhammadiyah sebagai Gerakan Tajdid di Kota Palangka Raya - Iqbal (Tumanurung: Jurnal Sejarah dan Budaya, 2025)
Muhammadiyah as a reformist movement in Indonesia is one of the movements that have existed since before the independence of Indonesian Republic. Since Muhammadiyah was established, Muhammadiyah has shown its contribution to development of Indonesian nation in all fields. Human as social beings will always develop from time to time, so that a renewal movement is needed so that Islam does not look rigid, so its suitable to be applied from time to time. Humans will always be dynamic so that human’s life changes from time to time. This is makes reformist organization like Muhammadiyah always be the reformost movement to answer the problems that arise in society. Therefore Muhammadiyah formulated two things related to the reform movement. The first, is the purification movement which is the purification movement of the beliefs of Moslems. The second, is the reform movement namely the development movement in understanding and implementing the religion of Islam which is in line with science and changes in society. In Palangka Raya, Muhammadiyah has contributed in several fields including education, religion leadership and social service. This article was written using a historical approach with analytical descriptive methods. In searching for sources, this article is an article that is compiled through interviews and reading literature that matches the title of article. Keyword : Muhammadiyah, reformist movement, Kota Palangka Raya